PENGARUH OPINI AUDIT, PERGANTIAN AUDITOR, AKTIVITAS PERSEDIAAN, DAN PANDEMI COVID-19 TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Rena Zahirah; Zumratul Meini (FEB-UP Press, 2022)
This study aims to obtain empirical evidence of the effect of audit opinion, auditor turnover, inventory activity, and the covid 19 pandemic on audit delay in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in 2016-2020. With predetermined criteria, the number of samples used is 32 companies with a total of 160 company-year observations. This research is novel by considering the COVID-19 pandemic as one of the factors that causes companies to experience audit delays in their financial reporting. The results show that audit opinion has no effect on audit delay, auditor turnover has a positive effect on audit delay, inventory activity has a negative effect on audit delay, and the COVID-19 pandemic has a positive effect on audit delay in manufacturing companies in the consumer goods industry sector listed on the Indonesian stock exchange. (IDX) 2016-2020 period Keywords: Audit Delay, Audit Opinion, Auditor Switching, Inventory Activities, Covid-19 Pandemic